XRD STRUCTURE STUDY ON NICKEL DOPED ZINC OXIDE NANOPARTICLES SYNTHESIZED BY COPRECIPITATION METHOD - Destalina, Destalina; Mujtahid, Fitriah; Mutmainna, Inayatul; Tahir, Dahlang; Gareso, Paulus L (Universitas Mataram, 2022)
Nickel-doped Zinc Oxide (Zn(1-x)Ni(x)O) nanoparticles have been synthesized by the chemical coprecipitation method. The structure and characteristic of synthesized Ni doped ZnO nanoparticles ware analyzed by X-ray diffraction (XRD) patterns. Crystallite sizes and lattice strain of all samples were calculated using the Scherrer’s formula, Uniform Deformation Model (UDM) and Halder-Wagner (H-W) method. X-ray diffraction analysis confirmed hexagonal cubic structure of Ni-doped ZnO nanoparticles. Also, the crystallite size of the nanoparticles reduces as the nickel concentration increase. The result showed the average crystallite size calculated by Scherrer’s formula (25-29 nm) was smaller than crystallite size using UDM method (51-63) the largest average crystallite size and H-W method (42-47 nm). The lattice strain increases with decreasing crystallite sizes value. The crystal size Ni- doped ZnO nanoparticles decreased with increasing dopant concentration.